Regime, reputation and resilience: the queer experience of Cape Town's single-sex schools - Cassells, Kirstin (African Studies, 2025)
The following research paper explores the experiences of self-identified queer past pupils of single-sex schools in Cape Town, South Africa. The intention of the study was to gain insights into the implicit and explicit psycho-social and systematic control felt by student bodies in highly-traditional school spaces, through the specific lens of queer students and their navigations of such spaces. The theoretical frameworks of Bourdieu's Social Reproduction Theory, the hidden curriculum, Freire's Critical Consciousness and hook's Engaged Pedagogy provide the theoretical foundation, in addition to Butler's Gendered Performativity. Research findings revealed the strict school environment, moulding an idealised archetype expected of the students, which aligned closely with heteronormative, middle-class, whiteness. This archetype was upheld through the hierarchy of academic excellence, internalised compliance, and strict boundaries of acceptable behaviour that were maintained through discipline and reward practices. Within this strict environment, queer students and educators were located through the accounts provided by participants. Their resilience, navigation and endurance of the school space are central to this dissertation. This study provides a clear example of Bourdieu's Social Reproduction Theory and the hidden curriculum at work in the school environment. The impact of pervasive heteronormative white hegemony, the remaining legacy of the white-dominated Apartheid system and the conservative societal expectations of gender performativity are revealed to have an ever-present role in the experience of single-sex schools in Cape Town.